INTERAKSI POLITIK ANTARA MUSLIM DAN NON MUSLIM MENURUT IBNU QOYYIM DAN FAHMI HUWAIDI - Sukandi Sukandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
This research is intended to reveal the political relationship between Muslims and non-Muslims. According to the worldview, the political interaction between Muslims and non-Muslims are only warfare is not peaceful. Those matter because the world has seen Islam from one aspect. The study found that in politics Islam who has two interactions. The first interaction is the political interaction is revealed by Ibn Qayyim al-Jawziyyah and the second interaction was the political interaction is expressed by Fahmi Huwaidi.